ON THE FORMATION OF A NATURAL HABITAT OF VIPERA LEBETINA [MACROVIPERA LEBETINA (LINNAEUS, 1758)] - Z. S. Ismailova (Юг России: экология, развитие, 2016)
The aim of the study is to analyze the area of Macrovipera lebetina (Linnaeus, 1758) in the historical past and in the present using published sources and the results of own researches as well as to give taxonomy of the species. Identify how the formation of species habitat due to the geological history of the formation of the Mediterranean landscapes, their distribution and the impact on neighboring regions. Moreover, to identify how the formation of species habitat is associated with the geological history of the formation of the Mediterranean landscapes, their distribution and the impact on neighboring regions.Results. It was revealed that the aridity of climate had a favorable impact on the distribution of this species in the eastern Caucasus. We also suggest typical habitat of M.l.obtusa.Main conclusions. Analyzed data on the distribution of lebetina viper in Dagestan has allowed delineating its habitat. It was found that its distribution is closely related to water sources and has a focal character. We have identified optimal habitats for this specie as well as limiting factors in the spread of this species in the region. Measures of protection have also been proposed.